Characterization, reproduction, and pathogenicity of Marasmiellus palmivorus (sharples) desjardin (comb. prov.) of oil palm in Peninsular Malaysia - Pong, Vui Mei (2013)
Oil palm (Elaeis guineensis) is an economically very important plantation crop in Malaysia. However, it is susceptible to various diseases including bunch rot causing severe losses and damage to oil palm fruit bunches. The causal agent previously identified to be Marasmiellus palmivorus has not been published well in literature. There is no description of the morphology and information on reproduction and pathogenicity of the species found in local oil palm plantations in Malaysia. Knowledge on the reproduction and pathogenicity is essential to facilitate further detailed study of this fungus. Rhizomorphs and basidiocarps found on dead fruits, fronds or trunks of oil palm were randomly sampled from plantations located in the states of Perak and Selangor. The fungus was isolated and repeatedly subcultured on Malt Extract Agar (MEA) to obtain pure culture. Hyphae were septate and found to produce clamp connections under light and scanning electron microscopy. Diameter of pileus was in the range of 0.5-2cm, stipe length ranged from 1-3.2cm. Each pileus was slightly depressed at the center, smooth, convex, with involute margin, orange-white fading to white and possess a central, solid, tough, cylindrical, overall whitish stipe. The gills were adnate, distant and have a non-distinctive odour. All isolates grew optimumly at the range of 25-30°C and pH range of 5.0-6.0 on MEA indicating that Marasmiellus palmivorus was a mesophile. Mycelial interaction test showed that isolates found were from three different mating types: Teluk Intan (Perak), Bangi (Selangor) and Serdang (Selangor). Induction of basidiocarps using wheat spawn was carried out in a moist growth chamber in a complete randomized design (CRD), with treatments of 12 hours of alternate white light and darkness contributed to fructifications on oil palm empty fruit bunch fibres substrates. Empty fruit bunch fibres substrates yielded better quality of basidiocarps with mean of 22 basidiocarps, mean diameter of pileus 2.7cm and mean length of stipe 0.6cm. Morphology of induced basidiocarps was similar to naturally produced fruit bodies. White spore prints were obtained. Average discharge of ellipsoid basidiospores per basidiocarp was 3.29 x 104 spores per milliliter (ml). Spores were viable with size of 6.2-8.7μm, 80-85% germination and germ tubes ranging from 64.3-82.5μm after 24 hours incubation at ambient temperature on water agar. Pathogenicity test of six representative isolates showed that M. palmivorus was able to cause necrotic lesions on wounded leaves of oil palm seedlings with disease incidence reaching up to 33-55%.